Perioperative cognition in association with malnutrition and frailty: a narrative review - Dammavalam, Vikalpa; Murphy, Jasper; Johnkutty, Meenu; Elias, Murad; Corn, Ryan; Bergese, Sergio (Frontiers in Neuroscience, 2023)
Postoperative delirium (POD) is a prevalent clinical entity characterized by reversible fluctuating altered mental status and cognitive impairment with acute and rapid onset a few days after major surgery. Postoperative cognitive decline (POCD) is a more permanent extension of POD characterized by prolonged global cognitive impairment for several months to years after surgery and anesthesia. Both syndromes have been shown to increase morbidity and mortality in postoperative patients making their multiple risk factors targets for optimization. In particular, nutrition imparts a significant and potentially reversible risk factor. Malnutrition and frailty have been linked as risk factors and predictive indicators for POD and less so for POCD. This review aims to outline the association between nutrition and perioperative cognitive outcomes as well as potential interventions such as prehabilitation.